1980
DOI: 10.1177/030098588001700609
|View full text |Cite
|
Sign up to set email alerts
|

The Effects of Clostridium perfringens Type A Enterotoxin in Shetland Ponies—Clinical, Morphologic and Clinicopathologic Changes

Abstract: Abstract. Severe abdominal pain, classic colic signs and hemorrhagic gastro-entero-cecocolitis were induced in three conventional Shetland ponies by intravenous injection with Clostridium perfringens Type A enterotoxin. Histological examination showed marked congestion, edema and hemorrhage of the large and small intestine and sloughing of the tips of the intestinal villi. Marked vacuolar degeneration of hepatocytes with dilatation of the spaces of Disse also was found. Clinical changes consisted of severe hyp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
5
0

Year Published

1985
1985
2018
2018

Publication Types

Select...
6
4

Relationship

0
10

Authors

Journals

citations
Cited by 20 publications
(5 citation statements)
references
References 8 publications
0
5
0
Order By: Relevance
“…i.v. inoculation of ponies with a culture of type A caused acute colic and hemorrhagic enterocolitis (303).…”
Section: Disease and Pathogenesis By Toxin Typementioning
confidence: 99%
“…i.v. inoculation of ponies with a culture of type A caused acute colic and hemorrhagic enterocolitis (303).…”
Section: Disease and Pathogenesis By Toxin Typementioning
confidence: 99%
“…Clostridium perfringens has been suggested to be an etiologic agent, but evidence is lacking. Intravenous injection of C. perfringens enterotoxin (CPE) produced colic, severe shock, and pathological changes typical of colitis X, 21 but enterotoxigenic strains are seldom recovered from cases (unpublished data). Furthermore, CPE is produced in the gut, and there is no evidence that it enters circulation.…”
mentioning
confidence: 99%
“…Type A is subdivided further into enterotoxigenic and nonenterotoxigenic strains (16). It has been reported that acute colic signs and hemorrhagic gastroenterocolitis could be induced experimentally in Shetland ponies after intravenous injection of enterotoxin obtained from enterotoxigenic C. perfringens type A (12). However, other studies showed that enterotoxigenic C. perfringens isolates do not play a role in intestinal disorders of horses (2).…”
mentioning
confidence: 99%